Metais e Não-Metais em Sedimentos de um Manguezal Não-Poluído, Ilha do Cardoso, Cananéia (SP) - Semensatto, Décio Luis [UNESP]; Araújo, Geórgia Christina Labuto; Funo, Rogério Hideki Ferreira [UNESP]; Santa-Cruz, Joana [UNESP]; Dias-Brito, Dimas [UNESP] (Universidade Federal do Rio Grande do Sul, 2007)
This work aims to assess the spatial distribution and the seasonal behavior of metals, no-metals, physical and chemical variables and provide a pre-impact geochemical scenario from non-polluted mangrove sediments of a transect at the Cardoso Island (Cananéia, São Paulo State, Brazil) extending 340 m long landward. Triplicate samples from eight stations were collected in December 2001 and June 2002. Conductivity, pH, temperature, salinity and dissolved oxygen from the sediment interstitial water were checked in field using a Horiba U-10 probe. Metals and no-metals concentrations were obtained employing an inductively coupled plasma optical emission spectrometer (ICP OES) Vista-RL-Varian, radial vision. The sediments reflected two distinct intertidal segments: a “lower plain” (LP) and an “upper plain” (UP). The LP, which comprises the first 100 m landward from the bay, is a muddy environment with higher metal concentration and seasonally more stable than the UP. This latter, extending until the upper boundary of the intertidal zone, is a more oxygenated sandy flat with lower metal concentration. The distinct behavior of the geochemistry pattern observed along the transect in December and June is interpreted as associated with seasonal pluviometric fluctuations. The low metal concentrations denote low anthropogenic interference in the area, one of the most well preserved Brazilian coastal regions. It can be used as reference area to comparative studies involving similar ecosystems and, in the future, to check the environmental state of this mangrove flat.
Keywords: geochemistry; mangrove; sediment